Analysis of overweight and obesity in menopausal women using bioelectrical impedance analysis system - Dąbrowska, Jolanta; Naworska, Beata; Dąbrowska-Galas, Magdalena; Wodarska, Magdalena; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Increased body mass is one of the biggest health problems among women aged 55-65. Obesity has been implicated as one of the major risk factors for coronary heart disease, diabetes and hypertension. Moreover, obesity can contribute to incontinence and musculoskeletal diseases, in particular osteoarthritis. This problem occurs more often in women than in men, therefore the health-related quality of life in menopausal women remains significantly lower in all physical, mental and sexual domains. The aim of the study was to present the current prevalence of overweight and obesity in menopausal women and to find out whether increased BMI (body mass index) is combined mainly with increased body fat mass. Material and methods: 136 women aged 45-65 from Silesia were included to the study. The average age of women was 57.35 ±6.18. A noninvasive, reliable and secure bioelectrical impedance analysis (BIA) system was used to evaluate the body composition. Results : 39.71% of women had normal body mass, 36.76% were overweight, and 23.53% were obese. Body fat percentage increased with age. The lowest body fat percentage has been reported in women aged 45-49 (32.15%), slightly higher in the group of 51-60-year-old women (32.28%) and the highest in women aged 61-65 (35.5%) (p = 0.028). Conclusions : Education and a healthy lifestyle promotion are necessary to reduce the problem of overweight and obesity in menopausal women. An increase in body mass in women during menopause is associated mainly with the increased body fat percentage.